PENGARUH EFEKTIVITAS PENGGUNAAN APLIKASI MOBILE DALAM MENINGKATKAN EFISIENSI PENGIRIMAN BARANG PADA PERUSAHAAN ACE HARDWARE SIDOARJO - Dwi Mei Riya Ristanti (Yos Soedarso Economic Journal (YEJ), 2023)
Very rapid technological developments and followed by high levels of economic growth and complex demand developments have resulted in the emergence of various kinds of industries that solely answer the needs of society. This makes competition in trade increasingly tighter and sharper, especially between companies that have the same type of characteristics. Based on the background of the problems explained above, the researcher concluded that problems occurred, namely that there were still activities that were less effective in carrying out company operations, mastery of the use of mobile applications that was still not comprehensive for every employee and the efficiency of delivering goods was still not optimal and still needed improvement. . This research aims to find out how mobile applications are used and the efficiency of goods delivery at the ACE Hardware Sidoarjo company. And to find out how big a role the use of mobile applications plays in the efficiency of goods delivery. The factors tested in this research are the use of mobile applications as the independent variable, while the efficiency of goods delivery is the dependent variable. The research method used in this research is descriptive and verification methods. The population in this study is all data from the ACE Hardware Sidoarjo store. The sampling technique used in this research is non-probability sampling with a saturated sampling method. Meanwhile, the data analysis used in this research is simple linear regression analysis at a significance level of 5%. The program used to analyze the data uses the Statistical Package for Social Sciences (SPSS) Ver 19.00. A hypothesis is an opinion, conjecture or theory that is still imperfect, or in other words, a hypothesis is a conclusion that is not final or still needs to be proven and tested for its truth. Therefore, based on research conducted by the author, the author takes a hypothesis. Using Mobile Application Technology can increase the effectiveness of transactions. as well as increasing the efficiency of goods delivery at the ACE Hardware Sidoarjo company. The research results show that the use of mobile applications and the efficiency of delivering goods has shown an increase. Apart from that, the research results also show that the large role of the use of mobile applications on goods delivery efficiency is 19.1%. Based on the results of the t test (partial) in the regression model, the significance value of the mobile application usage variable was obtained at 0.033<0.05. Apart from that, it can also be seen from the results of the comparison between tcount>ttable, namely 2.280>2.074, it can be concluded that Ha is accepted, meaning that partially the variable use of mobile applications plays a role in the variable efficiency of goods delivery.